RAHMAH EL YUNUSIYAH’S MODERNIZATION OF INDONESIAN WOMEN ULAMA FIGURES IN EDUCATIONAL - Atifah Hirahmah,; Dwi Rika Andriyani,; Muhammad Aizri Fadillah,; Fatni Mufit, (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2024)
This research aims to develop Rahmah El-Yunusiyah's ideas on education about the present time, by raising relevant topics under the demands of the 21st century. The approach used in this research is Library Research. The approach taken is to identify, review, evaluate, and interpret the research that has been done. This research method is by collecting related journal articles for this research report. Based on the research findings, Rahmah El Yunusiyah's perspective of Islamic Religious Education aims to teach men and women to learn about Islam from an early age until the end of life, a positive example, and under their respective times. The idea of the transformation of Islam pioneered by Rahmah El Yunusiyah and her relationship with society makes her ideas relevant to the 21st century. This becomes very important in the face of globalization which demands broad capabilities, especially in terms of connectivity. Rahmah El Yunusiyah's ideas on education need to be appreciated and researched further.